Unemployment Hysteresis in Middle-Income Countries - Boukraine, Wissem (Universitas Airlangga, 2021)
Business cycles pave the way for asymmetry in the unemployment rate behavior with rapid increases during recessions and slight decreases in expansions. It, in turn, may raise the non-accelerating inflation rate of unemployment and the cost in terms of inflation of any demand stimulus policy. The recent jump in unemployment worldwide due to the COVID-19 pandemic and the government's stimulus package following it raises questions about the cost of such a decision. We use the smooth transition model (STR) to analyze unemployment dynamics on quarterly data over the last two decades for fifteen middle-income countries. Our results suggest the absence of hysteresis except for Bulgaria, Mexico, and Ukraine. Our policy recommendation for these countries is the necessity of labor market reforms, as hysteresis will considerably reduce any economic stimulus on unemployment. Keywords: Unemployment, Hysteresis, STR JEL: C10, J60